(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2025)
In the Brazilian elections of 2018, 2020 and 2022, disinformation reached new heights, standing out as a central element in the public and academic debate. In light of these electoral processes, the National Network to Combat Disinformation (RNCD) produces and disseminates knowledge about the disinformation market in the country and around the world. To this end, the article analyzes the network’s performance and lists studies covered in the context of disinformation and elections. The research adopts an exploratory and bibliographical approach based on a state of the art, including scientific articles, theses, dissertations and periodical publications, presented in the Research and Publications section on the organization’s website. It is concluded that there is still a lack of bibliographical production on the topic of disinformation, especially when associated with elections in the RNCD database.